EVALUATION OF TOURISM INFRASTRUCTURE IN SUPPORTING THE WATERFRONT CITY CONCEPT IN PARAPAT - Tony Sirait; Abdi Sugiarto; Ruri Prihatini Lubis (RADJA PUBLIKA, 2025)
This study evaluates the readiness of tourism infrastructure in Parapat as a supporting area for the optimization of the Waterfront City concept in the Lake Toba region. Parapat plays a strategic role as the main gateway and tourism transit hub for visitors accessing waterfront development in Samosir Island. A mixed-methods approach was employed, emphasizing descriptive quantitative analysis supported by qualitative SWOT analysis. Primary data were collected through questionnaires distributed to tourists, field observations, and documentation of existing conditions, while secondary data were obtained from official publications and tourism planning documents. The evaluation focused on the availability of supporting facilities and the quality of area services as key indicators of infrastructure readiness. The results indicate that Parapat’s tourism infrastructure is at a moderately adequate level, characterized by the presence of lakeside public spaces, pedestrian paths, and basic supporting facilities. However, several aspects, including area legibility, service consistency, public facility accessibility, and cleanliness management, still require improvement. The SWOT analysis reveals that Parapat has strong potential to function as an effective supporting area for the Waterfront City development, provided that service quality enhancement and integrated area management are strengthened. This study highlights the importance of supporting areas in ensuring sustainable and coherent tourism experiences within priority destinations.